2022
DOI: 10.1111/jnc.15728
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocyte lineage cells: Advances in development, disease, and heterogeneity

Abstract: The oligodendrocyte lineage cells include oligodendrocyte progenitor cells (OPCs) and oligodendrocytes (OLs). OPCs are the precursor cells of OLs in the central nervous system (CNS). During development, OPCs terminally differentiate and mature into myelinated OLs (Guo et al., 2018;Micu et al., 2018). OPCs are distributed throughout the CNS and are characterized by the high expression of PDGFRα and NG2 on such cells (Dawson et al., 2003;Sim et al., 2011). The primary function of OPCs is to differentiate into ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
5
0
Order By: Relevance
“…These include astrocytes and microglia 20 , but, most importantly, the oligodendrocytes and oligodendrocyte progenitor cells 21 . Oligodendrocytes are post-mitotic cells that provide a myelin sheath for neurons, and it has been shown that oligodendrocytes undergo continuous turnover and are replaced by local tissue progenitors 22 , 23 . Depletion of these cells has been reported to occur as early as 3 days after irradiation 24 , ultimately resulting in demyelination and white matter loss, which are features typically associated with post-irradiation brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
“…These include astrocytes and microglia 20 , but, most importantly, the oligodendrocytes and oligodendrocyte progenitor cells 21 . Oligodendrocytes are post-mitotic cells that provide a myelin sheath for neurons, and it has been shown that oligodendrocytes undergo continuous turnover and are replaced by local tissue progenitors 22 , 23 . Depletion of these cells has been reported to occur as early as 3 days after irradiation 24 , ultimately resulting in demyelination and white matter loss, which are features typically associated with post-irradiation brain atrophy.…”
Section: Discussionmentioning
confidence: 99%
“… 20 Oligodendrocytes are post-mitotic cells that provide a myelin sheath for neurons, and it has been shown that oligodendrocytes undergo continuous turnover and are replaced by local tissue progenitors. 21 , 22 Depletion of these cells has been reported to occur as early as 3 days after irradiation, 23 ultimately resulting in demyelination and white matter loss, which are features typically associated with post-irradiation brain atrophy. Astrocytes are another important glial phenotype to consider.…”
Section: Discussionmentioning
confidence: 99%
“…Cell type proportion estimates were performed using Bisque deconvolution(81) of our RNAseq data using the Brain Initiative Cell Census Network 2.0(32) as the reference scRNAseq dataset. Clusters from Yao et al, 2023 were mapped onto the widely adopted nomenclature(15, 18, 66, 82, 83) used for oligodendrocyte lineage first defined by Marques et al, 2016 using the expression of marker genes in each cluster: clusters 5266-5271 = OPC, 5272-5277 = COP, 5280 = NFOL1, 5281 = NFOL2, 5283 = MFOL1, 5282 = MFOL2, 5288 = MOL1, 5284 & 5286 = MOL2/3, 5285 & 5287 = MOL5/6.…”
Section: Methodsmentioning
confidence: 99%
“…Cell type proportion estimates were performed using Bisque deconvolution(81) of our RNAseq data using the Brain Initiative Cell Census Network 2.0(32) as the reference scRNAseq dataset. Clusters from Yao et al, 2023 were mapped onto the widely adopted nomenclature (15,18,66,82,83)…”
Section: Bioinformaticsmentioning
confidence: 99%